Analysis of The Bank's Civil Liability For Employees' Tortious Acts Committed Outside The Bank's Operational System - Fauzan Hamzah Salampessy; Wardani Rizkianti (Journal of Law, Politic and Humanities, 2026)
This study examines the civil liability of Bank BNI regarding an unlawful act committed by the former Head of Cashier of the Aek Nabara Branch through an off-book transaction. The issues focus on the regulation of bank liability based on Article 1367 of the Indonesian Civil Code and POJK Number 6/POJK.07/2022, as well as the implementation of the principle of vicarious liability to employee actions that exceed the bank’s official operational systems. Employing a normative juridical method, this research concludes that the bank's liability stems from two complementary normative layers: Article 1367 paragraph (3) of the Civil Code as a general rule and Article 8 paragraph (1) of POJK Number 6/POJK.07/2022 as a sectoral regulation. Collectively, these regulations establish the bank as the party responsible for customer losses resulting from its employees' actions. The application of the doctrine of vicarious liability in this case is justified by the fulfillment of the employment relationship element and the doctrine of apparent authority, wherein the perpetrator objectively appeared as a bank representative to customers acting in good faith. Thus, Bank BNI's action to compensate for the customer's loss of IDR 28 billion is not merely a voluntary initiative, but rather a fulfillment of legal mandates rooted in the doctrine of vicarious liability and the fundamental principles of consumer protection within the financial services industry.